Parenting Pain Away: Development and usability testing of an educational website about infant procedural pain management - B. Hughes; R. Martin‐Misener; M. Latimer; M. Smit; P. McGrath; M. Campbell‐Yeo (Paediatric & Neonatal Pain)
Abstract All newborns undergo minor painful procedures (e.g., injections). Despite strong evidence supporting parents' efficacy to reduce procedural pain (e.g., breastfeeding), parents remain an underutilized resource. Limited evidence‐based resources about infant procedural pain management targeting parents in the perinatal period exist. We co‐created Parenting Pain Away, a website to enhance parents' access to information and participation in procedural pain management following birth. This study aimed to conduct iterative usability testing with the perinatal population to refine Parenting Pain Away based on target users' identified needs and satisfaction. In 2020, parents of healthy newborns or expectant parents from an Atlantic Canadian province, participated in two iterative cycles of usability testing of Parenting Pain Away. Through recorded interviews, participants were directed to use the “Think Aloud” approach (e.g., verbalize what they see, think, feel) as they navigated through the website. Participants completed online questionnaires related to demographics and user satisfaction, measured by the Post Study System Usability Questionnaire (PSSUQ). Descriptive statistics and content analysis were conducted to analyze the data. In total, there were 10 participants with an average age of 29.9 years (SD = 3.9). Participants identified as mothers (n = 7) or fathers (n = 3) and were expecting (n = 6) or had a newborn (n = 4). The PSSUQ overall scores were 1.84 (SD = 0.55) and 1.34 (SD = 0.49) in Cycles 1 and 2, respectively, indicating high user satisfaction on the 7‐point scale. When comparing between the two cycles, the average overall score was lower in Cycle 2, suggesting improved satisfaction. Participants provided positive feedback about the website and suggested major refinements to simplify content and site navigation. Findings from usability testing cycles were used to inform refinements of the Parenting Pain Away in response to participant satisfaction and feedback. Engaging target users in the development process enhanced this website in preparation for further effectiveness testing.